Ejen Ali and worldbuilding: The case of transmedia production in Malaysian animation industry / Umar Hakim Mohd Hasri - Umar Hakim , Mohd Hasri (2024)
This study examines Ejen Ali franchise, a prominent Malaysian animation series, through the lens of transmedia storytelling and worldbuilding theories. Utilizing a qualitative case study approach, this research delves into how Wau Animation, the franchise's primary producer, orchestrates content across various media formats to extend the narrative universe of Ejen Ali. The study investigates the integration of diverse media platforms in narrative construction and the practical strategies employed by the production team to align theoretical frameworks with actual production practices. By focusing on the interplay between transmedia storytelling and worldbuilding, this research highlights the mechanisms through which Ejen Ali's storyworld is constructed and expanded. Furthermore, it situates these findings within the broader context of the Malaysian animation industry, offering insights into local practices and their contribution to the global understanding of transmedia narratives. Through interviews and content analysis, this study illustrates the exploratory and collaborative nature of worldbuilding implemented by Wau Animation in the development of Ejen Ali franchise as transmedia content. The findings of this study not only map the transmedia features of Ejen Ali but also bridges the gap between academic theory and industry practice, enhancing the clarity and relevance of transmedia studies within a Malaysian context.